GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SOSIAL DAN KINERJA OPERASI PERUSAHAAN DALAM SRI-KEHATI INDEX - Sri Pujiningsih; Helianti Utami (Jurnal Keuangan dan Perbankan, 2011)
There were many controversion arguments about the implementation of corporate social responsibility (CSR)in the company rule no 40, 2007. Moreover, in June 8, 2009, BEI and KEHATI Foundation published Indexof SRI-KEHATI. It consisted 25 of the best shares companies that had applied CSR. It was one of implementationsof GCG. Based on those reasons, there were three aims of this research. First, this research tested thesignificant influence of GCG to the level of CSR disclosure. Second, this paper examined the significant effectof GCG to the operational performance (ROA). The last aim was that the significant impact of GCG to theoperational performance (ROA) by CSR. In this research,the proxy of GCG was the independent board ofdirectors and institutional ownership. Respondents participating in this research were companies in Index ofSRI-KEHATI. This research used purposive sampling method with 16 samples. Analysis used path analysisto examine three hypotheses. There were three result of this research. First, GCG did not have significantinfluence to the level of CSR disclosure. Second, GCG did not have significant influence to the operationalperformance (ROA). Third, GCG had significant influence to the ROA by CSR.